2013
DOI: 10.1007/s00382-013-1772-2
|View full text |Cite
|
Sign up to set email alerts
|

Predictable patterns and predictive skills of monsoon precipitation in Northern Hemisphere summer in NCEP CFSv2 reforecasts

Abstract: The predictable patterns and predictive skills of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 36 publications
2
31
0
1
Order By: Relevance
“…The most successful deterministic predictions of monsoon systems to date consist of predicting the large-scale component of the flow, defined as the primary modes of variability (Zhou and Zou, 2010;Zuo et al, 2013;Wang et al, 2015). However, regional features of monsoon precipitation anomalies remain highly unpredictable (Zhou and Zou, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The most successful deterministic predictions of monsoon systems to date consist of predicting the large-scale component of the flow, defined as the primary modes of variability (Zhou and Zou, 2010;Zuo et al, 2013;Wang et al, 2015). However, regional features of monsoon precipitation anomalies remain highly unpredictable (Zhou and Zou, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a larger variance of the MSN EOF mode indicates higher predictability, and the leading MSN EOF modes represent the most predictable patterns. The MSN EOF method has been applied successfully to the ensemble hindcasts to extract their predictable signals for different variables and in different areas (e.g., Hu and Huang 2007;Liang et al 2009;Zuo et al 2013;Zhu et al 2015). Different from most previous MSN EOF applications, which usually target at a particular month or season, our analysis is applied to hindcasts for every calendar month to examine the evolution of the predictable patterns within a full annual cycle.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have investigated prediction and predictability of the climate variations within the Indo-Pacific region under the seasonal framework (e.g., Wang et al 2005;Yuan et al 2011;Jiang et al 2013a;Zuo et al 2013;Jia and Lin 2013;Yang and Jiang 2014). For instance, Liang et al (2009) found that the first and second most predictable patterns of the Asian and Indo-Pacific summer precipitation are characterized by different climate features of the onset and decay years of ENSO, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The CFSv2 has good simulation and prediction skill for SSTA in the tropical Pacific associated with ENSO (Zhu et al 2012;H.-M. Kim et al 2012;Xue et al 2013) and reasonable prediction skill for SSTA in the North Atlantic , for U.S. climate (Zhu et al 2013) and for global monsoons (Zuo et al 2013). For the ocean model, there are 40 levels in the vertical direction, to the maximum depth of 4737 m. The horizontal resolution of MOM4 is 0.258 in the tropics, tapering to a global resolution of 0.58 poleward of 108N and 108S, respectively.…”
Section: Datamentioning
confidence: 99%